2004
DOI: 10.1083/jcb.200301106
|View full text |Cite
|
Sign up to set email alerts
|

The p75NTR-interacting protein SC1 inhibits cell cycle progression by transcriptional repression of cyclin E

Abstract: Schwann cell factor 1 (SC1), a p75 neurotrophin receptor–interacting protein, is a member of the positive regulatory/suppressor of variegation, enhancer of zeste, trithorax (PR/SET) domain-containing zinc finger protein family, and it has been shown to be regulated by serum and neurotrophins. SC1 shows a differential cytoplasmic and nuclear distribution, and its presence in the nucleus correlates strongly with the absence of bromodeoxyuridine (BrdU) in these nuclei. Here, we investigated potential transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 55 publications
2
56
0
Order By: Relevance
“…4). It has been reported that the PR and ZF domains are required for Prdm4 to inhibit the cell cycle through the transcriptional repression of cyclin E (Chittka et al, 2004). Therefore, the properties of Prdm12 we demonstrated are similar to other Prdms.…”
Section: Discussionsupporting
confidence: 55%
“…4). It has been reported that the PR and ZF domains are required for Prdm4 to inhibit the cell cycle through the transcriptional repression of cyclin E (Chittka et al, 2004). Therefore, the properties of Prdm12 we demonstrated are similar to other Prdms.…”
Section: Discussionsupporting
confidence: 55%
“…We propose that activation of p75 NTR on SVZ precursors favors neuroblast generation, a function consistent with the ability of p75 NTR to promote cell cycle progression and terminal differentiation in other systems (Cattaneo and McKay, 1990;Seidl et al, 1998;Lachyankar et al, 2003). For example, neurotrophin-stimulated signaling has been shown to act through downstream p75 NTR -interacting proteins, such as Schwann cell factor-1, to promote withdrawal from the cell cycle (Chittka and Chao, 1999;Chittka et al, 2004) and facilitate the expression of differentiation-promoting genes (Ito et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…[76]). A number of intracellular proteins that control various aspects of the cell cycle, including Schwann cell factor-1 (Sc-1), brain-expressed X-linked 1 (Bex1) and melanoma antigen gene (MAGE) proteins, interact with the ICD of p75 NTR , and are found in the nucleus after ligand activation of p75 NTR [79][80][81]. The p75 NTR -interacting protein, NRIF, has been found in the nucleus with the ICD of p75 NTR following RIP [17], and RIP is required for p75 NTR -dependent Amyloid b-induced neurogenesis [82].…”
Section: In Cycling Cells P75mentioning
confidence: 99%